The Influence of Work Discipline on Employee Performance at the Takalar Regency PDAM Office - Muh Fahmi Fatha; Zalkha Soraya; Ruliaty, Ruliaty (CV. AFDIFAL MAJU BERKAH, 2024)
This research is a type of quantitative research with the aim of finding out the effect of work discipline on employee performance at the Takalar Regency PDAM Office with a population of 45 employees and a sample of 45 employees. This sample was taken from the Takalar Regency PDAM Office. The type of data used in this research is quantitative data obtained from distributed questionnaires and is related to the problem being studied. In this research, the data sources used in data collection include primary data and secondary data. The research instrument used in this research used the Likert Scale method. Based on the results of data research using statistical calculations through applicationsStatistical Package For the Social Science (SPSS) version 29 regarding the influence of work discipline on employee performance at the Takalar Regency PDAM Office which was discussed in the previous chapter, the author draws an important conclusion, namely that work discipline has a positive and significant effect on employee performance with an influence of as much as93.2% while 6.8% was influenced by other variables not examined in this study.Existing work discipline must be maintained because it can be seen from the research results that existing work discipline is very strong.